(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2026)
This tutorial shows how to build beautiful maps using polygon data of language distributions and the geospatial software QGIS. For this purpose, I show in the first part how to extract a list of Glottocodes from CLDF datasets and how to use command-line tools to extract the polygon data from Glottography datasets. The second part focuses on the visualization of the extracted data with QGIS. In this part, I also show to include non-linguistic data like archaeological sites and how to prepare the map for printing. The tutorial is fully implemented with free and open software and intends to make map-making accessible for linguists and other researchers.